Análisis jurídico y doctrinario de la política criminal aplicada por el estado ecuatoriano para prevención del delito de enriquecimiento ilícito - Sosa Pineda, Adriana Katherine (2023)
This Curricular Integration Work is entitled: "LEGAL AND DOCTRINAL ANALYSIS OF THE CRIMINAL POLICY APPLIED BY THE ECUADORIAN STATE FOR THE PREVENTION OF THE CRIME OF ILLICIT ENRICHMENT." Its execution is feasible to know the criminal policy that the governments in power have dictated for the prevention of the crime of illicit enrichment, finding its typification in the year 1985 within the criminal framework to deal with political corruption and contemplate it in international instruments such as the United Nations Convention against Corruption, of which Ecuador is a party. The excessive desire on the part of the civil servant to increase his patrimony at the expense of the public administration not only reveals the execution of the immoral act of disposing of the State's economic resources; but also demonstrates to society a weak, inefficient, ineffective, and obscure public management. The United Nations, through the Sustainable Development Goals, seeks to balance and eradicate large-scale corruption; for which it has proposed that the States parties adhere to the objectives and goals, which correspond to combating corruption in public and private companies; Likewise, Ecuador has foreseen the National Development and Opportunities Plan, trying to control and punish those responsible for committing illicit enrichment and taking advantage of State resources. As criminal policies used by governments, the reform of the Comprehensive Organic Criminal Code has been provided, not requiring a prior report from the Comptroller's Office to activate the public criminal exercise of the Prosecutor's Office in previous investigations; Likewise, it limits the right to change the semi-open and open regime of those sentenced for crimes of illicit enrichment. For the development of this research, we used inductive, deductive, analytical, synthetic, historical, comparative, and statistical methods. Within the research techniques, there is a bibliography collected from primary and secondary data that, after their respective documentary analysis, were included in each component of the Curricular Integration Work; with the analysis of the study cases, we identified that the offenders faced sentences for illicit enrichment. The Curricular Integration Work presented also includes a legal proposal to implement effective criminal policies that correct the flaws detected and prevent and combat corruption in public administration.